Dialogue between Mathematics Education and Education: problems and synergies - Faggiano, Eleonora; Fiorentino, Michele Giuliano; Montone, Antonella; Pertichino, Michele; Rossi, Pier Giuseppe (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
The didactic action is an holistic process in which general didactic (GD) and disciplinary didactic (DD) interact. But, how are they related? Two different modes occurred in the past: distinguishing between knowledge and education or removing one of the poles. This work attempts to overcome these two opposite solutions. The two discipline, GD and DD, impact on the same didactic action and each of them acts on the same aspects, although with different perspective. This synergy allows a plural analysis otherwise flawed. In order to gather problems and synergies of a plural analysis, this work analyses a research project, concerning a math teaching sequence for Primary School pupils, which involved researchers of the two disciplinary areas (GD and DD).